Changes In Protein Content In The Muscle Of Mystus cavasius (Ham) Exposed Electroplating Industrial Effluent Chromium - Palanisamy, P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Protein content in the muscle of Mystus cavasius (Ham) exposed to 1/3 of sublethal concentration of electroplating industrial effluent chromium (0.25%) for period of 30 days has been studied. After 24, 48, 72 hrs and 15 days of exposure the muscle showed significant depletion from -9.77%, -20.45%, -26.14% and -31.82% over the control.